Dietary fiber consumption and its relationship with anxiety and depression traits in adults from the ecuadorian highlands during the COVID-19 emergency - Abril Merizalde, Dennys Leonardo (2021)
Introduction: During the period of confinement due to the Coronavirus disease 2019 (Covid-19), both food consumption and the emotional functionality of the population have been affected and modified as an adaptation response to the provisions of local governments. Objective: To analyze the consumption of dietary fiber and its relationship with anxiety and depression traits in adults in the ecuadorian sierra region during this health emergency. Metodology: Cross-sectional design study, made up of a sample of 170 adults of both sexes, who were surveyed online during April and May. The instruments for data collection were a frequency of consumption of food sources of fiber and the Kessler-K10 scale of psychological distress. Results: There is no evidence of a relationship between fiber consumption and anxiety and depression traits. In the legumes group, cereals, tubers and nuts, there is evidence of a consumption in adequate frequency and quantity in both sexes, as for fruits and vegetables in both sexes the recommendation is not met. Regardless of sex, occupation, home area and consumption of food sources of dietary fiber, the population presents moderate anxiety and depression features according to the Kessler scale. Conclusion: The change in the diet of the young adult population during confinement has been favorable in terms of the consumption of dietary fiber, a situation that could constitute a protective factor for the development of emotional disorders and a benefit for the immune system.